2014
DOI: 10.1007/s12160-014-9639-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Prediction of Metabolic Burden from Physiological Responses to Stress

Abstract: Cardiac autonomic responses to stress predict future metabolic abnormalities, though the direction of effect differs according to sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 100 publications
2
16
0
2
Order By: Relevance
“…A 10-min baseline period ensued, during which subjects rested quietly, followed by a blood draw. Participants were then exposed to a laboratory stress protocol that included four 5 minute interpersonal stressors, each followed by 5-minute post-stress (recovery) periods (for details of the stress protocol see [55]). Following the laboratory visit, ambulatory BP and ECG were obtained during a 24-h period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10-min baseline period ensued, during which subjects rested quietly, followed by a blood draw. Participants were then exposed to a laboratory stress protocol that included four 5 minute interpersonal stressors, each followed by 5-minute post-stress (recovery) periods (for details of the stress protocol see [55]). Following the laboratory visit, ambulatory BP and ECG were obtained during a 24-h period.…”
Section: Methodsmentioning
confidence: 99%
“…BP, heart rate (HR) and heart-rate variability (HRV); high frequency heart rate variability (HF-HRV), normalized high frequency (HFnu), low frequency (LF-HRV), and ratio (LF/HF)) readings were averaged over each baseline, stress, and post-stress period. The four stress periods were averaged to create a composite stress and post-stress score, as per our prior research (see for more details see [55, 59]. Stress reactivity (stress−baseline) and recovery (post-stress score−baseline) change scores were then created as per established methods [71].…”
Section: Methodsmentioning
confidence: 99%
“…However, this was only the case for absolute values during the stress task and not for stress reactivity values. To our knowledge, only one previous study aimed to determine the predictive value of autonomic responses to psychological laboratory stress for development of metabolic burden (Gentile et al, 2015). The results indicated that parasympathetic withdrawal in response to stress was associated with an increased metabolic burden in men, but not women.…”
Section: Introductionmentioning
confidence: 92%
“…Данные имеющихся исследований свидетельствуют о том, что активация ФРН ассоциируется преимущественно с активной реакцией на стресс [7,10,11], в состоянии же выраженной депрессии его уровень существенно снижается [9,14]. То, что лица, страдающие абдоминальным ожирением и МС, характеризуются именно активным вариантом реагирования на стрессорную ситуацию [22][23][24], может быть одним из факторов, обусловливающих значительно более высокий уровень ФРН при АГ в сочетании с ожирением по сравнению с АГ без ожире- (p<0,05). ФРН -фактор роста нервов; ВАР -вариабельность; ДАД -диастолическое артериальное давление; САД -систолическое артериальное давление; СМАД -суточное мониторирование артериального давления.…”
Section: Discussionunclassified